Школа Сказок: [роман] / Ирина Эльба, Татьяна Осинская - Эльба Ирина (Академия Магии, 2015)
Экземпляры: ф.8 (20181107) / Инвентарный номер: 58862 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Э 53 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445